Effects of blood extraction on the mortality of Malaysian horseshoe crabs (Tachypleus gigas) - John, Akbar; Khan Chowdhury, Ahmed Jalal; Kasim, Zaleha; Amstrong, Peter B.; Yunus, Kamaruzzaman (Taylor & Francis, 2011)
Horseshoe crabs provide the important biomedical products, Limulus Amebocyte Lysate (LAL) and Tachypleus Amebocyte Lysate (TAL), which are produced by lysing the blood cells (amebocytes) using endotoxin-free distilled water. LAL/TAL is used to detect and quantify lipopolysaccharide (endotoxin), an important toxin of Gram-negative bacteria. Horseshoe crabs are the sole source for LAL/TAL and their fishery for the production of LAL/TAL is of concern to the sustained management of the species. This study investigated the mortality of the Malaysian horseshoe crab (Tachypleus gigas) related to blood extraction, with the aim of providing a basis for the sustainable management of the local fishery of this animal. We showed that the mortality rate of T. gigas due to the bleeding process is slightly higher than the values which has previously been reported for its conspecific, the American horseshoe crab (Limulus polyphemus). Overall mortalities of bled horseshoe crabs were 17.8% (male = 18.75%; female = 17.2%), while mortalities of unbled crabs were 3.5%. The quantification of the mortality due to the extent of bleeding commensurate with the commercial production of LAL/TAL provides a basis for the rational management of T. gigas in situations where harvest for LAL/TAL production is imposed on local populations of the animal.